Absorption of Cadmium and its Effect on the Growth of Halfsib Family of Three Cocoa Clones Seedling - Zakariyya, Fakhrusy; Iman Santoso, Teguh; Abdoellah, Soetanto (Indonesian Coffee and Cocoa Research Institute, 2022)
The issue of cadmium in cocoa beans has become one of the primary considerations in setting quality criteria in chocolate-consuming countries. Using rootstock genotypes that are tolerant to cadmium uptake can provide data on the absorption of cadmium into shoots for recovery. This study examined cocoa plants’ growth and physiological response to cadmium (Cd) accumulation. The research was carried out using polybags in the Greenhouse of the Indonesian Coffee and Cocoa Research Center using a half-sib family of cocoa aged 4 months after sowing. The study was designed using a completely randomized split-plot design with 3 replications. The parent plots were the half-sib families of Sulawesi 1, Sulawesi 2, and Scavina 6. The subplots were added with cadmium solution at 0 (control), 2, 4, and 8 ppm. The results showed that adding cadmium up to 8 ppm did not affect the growth and biomass of cocoa seedlings; however, it had a negative effect on plant physiological processes of the net assimilation rate and relative growth rate. Cadmium content in the tissue increased with increasing cadmium concentration in the growing medium. The accumulation of cadmium in roots was higher than that of shoots. Absorption of cadmium in the root tissue of Sulawesi 1 was higher than that of Scavina 6 and Sulawesi 2; genetic factors did not affect cadmium uptake in the shoots. There was a positive correlation between root dry weight and cadmium concentration in the tissue; the higher the dry weight of the root tissue, the higher the cadmium uptake in plants.